Rare Case of Servelle Martorelle Syndrome - Bhatnagar, A; Deshpande, M (Kathmandu University Medical Journal, 2014)
Servelle Martorelle Syndrome is a congenital vascular malformation associated with soft tissue hypertrophy and bony hypoplasia. This rarely involves whole of an extremity, with involvement of part of limbs reported in literature. We present a case of a twelve year boy who presented to the Department of Plastic Surgery SGPGIMS in April 2011 ,with history of circumferential soft tissue hypertrophy involving whole of left upper limb, scapular region and axilla since birth. The entire left upper limb length was lesser than the right upper limb. Hence this is a very rare case of Servelle Martorelle Syndrome having extensive limb involvement at a very young age. Highlighted is the role of conservative treatment and close follow-up to understand the natural history of the diseases, with prompt treatment of complications. DOI: http://dx.doi.org/10.3126/kumj.v10i4.11011 Kathmandu Univ Med J 2012;10(4):91-94